El arbitraje en la solución de controversias por indeterminación de precio en los contratos de compraventa internacional de mercancías. - Rogel Perez, Carolina Paola (My University, 2019)
International Arbitration is an optional element in the resolution of disputes for breach of contracts previously established by the buyer and seller. At an international level, this system is operated by the International Arbitration Center, which carries out its functions independently of the International Chamber of Commerce, having as a legal rule only the Arbitration Rules of the International Chamber of Commerce; that is why it was established as an objective, to identify the applicable commercial arbitration procedure, for the solution of disputes for breach of the contract, in terms of indetermination of the price, based on the international legal framework. The methodology applicable to this work is qualitative, which is essentially based on the study of legal documents and bibliographic articles (papers). In turn, it resulted in the procedure for the resolution of disputes is detailed, precise and clear within the Regulations of the International Chamber of Commerce, and, in turn, in the United Nations Convention on Contracts for International Sale of Goods was found the respective actions that the buyer must meet for breach of contract raised in the reagent.
El arbitraje internacional es un medio para la solución de controversias en el ámbito de los contratos de compraventa internacional de mercancías. Este sistema es operado, entre otras instituciones, por el Centro de Arbitraje Internacional, adscrito a la Cámara de Comercio Internacional, teniendo como norma jurídica básica de referencia el Reglamento de Arbitraje de la Cámara de Comercio Internacional. Este trabajo tuvo como objetivo, identificar el procedimiento de arbitraje comercial aplicable, para la solución de controversias por la causal de incumplimiento del contrato producido por la indeterminación del precio. La metodología aplicable en el presente trabajo fue cualitativa, de análisis documental y jurídico. Tuvimos como resultado que el procedimiento para la resolución de controversias está detallado en el Reglamento en referencia, y, a su vez, la Convención de las Naciones Unidas sobre los Contratos de Compraventa Internacional de Mercancías. Ambas fuentes jurídicas establecen el procedimiento y la regla aplicable para la solución de la controversia planteada en el reactivo.
Keywords: ARBITRAJE INTERNACIONAL; INCUMPLIMIENTO DE CONTRATO; PACTO ARBITRAL; LAUDO ARBITRAL